Analisis Keberlanjutan Agroindustri Ikan Lemuru (Sardinella sp.) (Studi Kasus di Kecamatan Puger, Kabupaten Jember) - Purnomo, Bambang Herry; Wibowo, Yuli; Suryaningrat, Ida Bagus; Novijanto, Noer; Suryadharma, Bertung; Fahmi, Achmadi Anwarul Anwarul (JURNAL AGROTEKNOLOGI, 2024)
The capture fisheries agroindustry faces serious business sustainability threats in the future, both from economic, resource, environmental, technological and social aspects. Lemuru fish (Sardinella sp.) based agroindustry in Puger District, Jember Regency also faces a similar threat. This research aims to analyze the sustainability of the lemuru fish processing business and provide recommendations for improving its sustainability. The analytical method used is Rapfish (Rapid Appraisal for Fisheries), while the recommendations are prepared descriptively. The results of the analysis show that the Lemuru agro-industry sustainability index is in the less sustainable category with a score of 42.61. The environmental dimension has the lowest index value in the bad category, followed by the social and technological dimensions which are categorized as less sustainable, while the resource and economic dimensions are categorized as quite sustainable. Efforts to improve the environmental dimension can be made by organizing mentoring programs to develop environmental management efforts. For the social and technological dimensions, technological guidance, management and horizontal diversification of processed lemuru waste can be carried out into various innovative products. Keywords: capture fisheries, lemuru, sustainability analysis, Rapfish